THE EFFECT OF DURIAN PEEL BOKASHI ON GROWTH AND RESULT OF RED OKRA IN ALLUVIAL SOIL - sitorus, ade ruth; ., purwaningsih; ., radian (Fakultas Pertanian Universitas Tanjungpura, 2020)
The durian peel can be used as bokashi material. This study aims to find the best dosage of durian peel bokashi on the growth and yield of red okra plants in alluvial soil. The study was conducted at Experiment Garden of Agriculture Faculty , Tanjungpura University. The research was started from May 20 to August 2, 2019. This study was used CRD (Completaly Randomized Design) method with 5 treatments, 5 replications and each treatments consists of 4 samples, there were 100 experiment units. The observed data were analyzed statistically by using Analysis of Variant (ANOVA), then continued by honestly significance diffirence (HSD) at 5% level. The result of this study showed that the durian peel bokashi with 270 g/polybag dosage could increased plant height at 5 WAP (Weeks after planting), number of fruit per plant and fruit weight per plant.Keywords: Durian peel bokashi, dosage, red okra, alluvial soil